Spirituality in the Context of Nonverbal Autism: A Research Process - Analysis and Findings - Hills, Karenne (Journal of disability & religion, 2019)
Communication issues and social idiosyncrasies create barriers to the inclusion of people with severe (nonverbal) autism into standard societal expectations. This paper reports the results of a study that explored the spirituality of this group, who are unable to express typical religious/spiritual understanding. Participants revealed a sophisticated and deeply considered spirituality. Despite misconceptions that they are unintelligent and incapable/unwilling to connect with others, participants also demonstrated an astute intelligence and desire to meaningfully participate in society. The need for support and care inclusive of appropriate participation for this population in faith communities and in the broader community is highlighted.